Studies on character association in fenugreek (Trigonella foenum-graecum L.) - N Hariprasada Rao, C Sarada, K Giridhar (Journal of Spices and Aromatic Crops, 2017)
The investigation was carried out with twelve genotypes of fenugreek obtained from differentcoordinating centres of AICRP on Spices at Regional Agricultural Research Station, Lamduring 1998-1999, 1999-2000, 2000-2001 and 2001-2002 to estimate the correlation coefficientsfor yield and yield components. The mean data over four years was subjected to statisticalanalysis for estimating correlation coefficients both at phenotypic and genotypic level. Ingeneral the phenotypic correlation coefficients were smaller than genotypic correlationcoefficients for majority of the characters. Seed yield showed highly significant positiveassociation with plant height (0.907** and 0.967**), number of pods per plant (0.876** and0.952 **), pod length (0.839** and 1.005**) and number of seeds per pod (0.905** and 0.984**)both at phenotypic and genotypic level, respectively. Among the yield component charactersplant height with number of pods per plant (0.961** and 0.971**), pod length (0.818** and0.939**), number of seeds per pod (0.982 and 0.994); number of pods per plant with podlength (0.743**, 0.932**), number of seeds per pod (0.979**, 0.994**) and pod length withnumber of seeds per pod (0.815**, 0.979**) showed significant positive association both atphenotypic and genotypic level.The phenotypic and genotypic correlation studied showed that association of seed yieldwith plant height, number of pods per plant, pod length and number of seeds per pod wasappreciable, indicating the importance of these traits as components for seed yield.